The Dead Sea scrolls in context : integrating the Dead Sea scrolls in the study of ancient texts, languages, and cultures - Lange, Armin, 1961-; Tov, Emanuel.; Weigold, Matthias. (Vetus Testamentum, Supplements, 2011)
The Dead Sea Scrolls enrich many areas of biblical research, as well as the study of ancient and rabbinic Judasim, early Christian and other ancient literatures, languages, and cultures. With nearly all Dead Sea Scrolls published, it is now time to integrate the Dead Sea Scrolls fully into the various disciplines that benefit from them. This two-volume collection of essays answers this need. It represents the proceedings of a conference jointly organized by the Hebrew University of Jerusalem and the University of Vienna in Vienna on February 11-14, 2008.